Analisis Struktur Genetik dan Filogenetik Bakteri Lactobacillus Plantarum yang Diisiolasi dari Produk Pangan - Karni, Ine; Nalurita, Indah; Gemma Pravitri, Kartika; Naufali, Muhammad Nizhar; Meikapasa, Ni Wayan Putu (LPPM Universitas Terbuka, 2024)
Lactobacillus plantarum (L. plantarum) is a type of Lactic Acid Bacteria (LAB) that can convert glucose into lactic acid. L. plantarum can mostly be found in milk, meat, fermented vegetables, and the human digestive tract. The L. plantarum bacteria has several strains, each of which has a good function in food fermentation and health. To understand the historical development of an organism's evolution, it is necessary to use phylogeny as the basis for systematic science in biological evolution. The aim of this research was to determine the genetic structure and level of relationship between L. plantarum bacteria isolated from food products. The data used in this research is secondary data taken from GenBank in the form of nucleotide sequences from the bacterium L. plantarum which were then analyzed using clustal W in the Bioedit application, then genetic and phylogenetic structure analysis was carried out using the MEGA 7 application. The results showed that the probability of substitution was the highest. detected in base G, followed by bases A, T/U, and C. The L. plantarum strain that has the highest level of relationship is the strain with GenBank codes AY424355.1 and AJ640082.1 with a bootsrep value of 99. The resulting phylogenetic tree topology is monophyletic, which means that all members in the group come from a common ancestor who passed on genetic, morphological and biochemical characteristics to his descendants.